The Role of Response Times on the Measurement of Mental Ability - Sideridis, Georgios; Alahmadi, Maisaa Taleb S. (Frontiers in Psychology, 2022)
The goal of the present study was to evaluate the roles of response times to the achievement of students in the following latent ability domains: (a) verbal, (b) math and spatial reasoning, (c) mental flexibility, and (d) scientific and mechanical reasoning. Participants were 869 students who took on the Multiple Mental Aptitude Scale. A mixture item response model put forth by Jeon and De Boeck (2020) was implemented to evaluate the roles of response times in performance by modeling ability and non-ability classes. Results after applying this model to the data across domains indicated the presence of several behaviors related to rapid responding which were covaried with low achievement likely representing unsuccessful guessing attempts.